Comparison of Spot Vision Screener and Retinoscopy for Detecting Refractive Errors in Children and Adults in a Tertiary Care Eye Hospital - Bhandari, Sangita Sharma; Bhandari, Gopal; Bhardwaj, Gaurav Kumar; Shrestha, Manisha; Adhikari, Ankita; Keenan, Jeremy (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Hand held photoscreeners are found to be useful for detecting significant refractive error and amblyopic risk factors in very young, preverbal and children with disabilities. Our study aims to determine the accuracy of spot vision screener compared to retinoscopy in screening refractive errors in both children and adults. Methods A total 388 eyes of 194 patients, 113 adults and 81 children underwent refractive error measurement through retinoscopy and spot vision screeners. Comparison of the findings of dry retinoscopy and spot vision was done for both adults and children. Cycloplegic comparison was done for children. Bland-Altman analysis was done to determine the limit of agreement between the measurements of two methods. Results The mean difference in spherical equivalent between spot vision screener and dry retinoscopy among both eyes of 113 adults was 0.08±0.18D. Among both eyes of 81children administered non-cycloplegic refraction the mean difference was 0.19±0.28D.A total of 25 children had both dry and wet refraction; among these children the mean difference before cycloplegia was 0.25±0.21D and the mean difference after cycloplegia was 0.05±0.40D. Bland-Altman analysis showed a good agreement between both methods in adults and children. Conclusions The spot vision screener showed no significant difference both clinically and statistically in both adults and children, with more accurate in children after cycloplegia. Spot vision screener can be used as a tool for screening refractive errors, but still retinoscopy with subjective refinement should be considered as the gold standard for refractive error correction.